Implementation of genomic medicine in Sri Lanka: Initial experience and challenges - Sirisena, Nirmala D; Neththikumara, Nilaksha; Wetthasinghe, Kalum; Dissanayake, Vajira H W (Applied & translational genomics, 2016)
The recent advances in next generation sequencing technologies have made it possible to implement genomic medicine in developing countries such as Sri Lanka where capacity for utilization is limited. This paper aims to describe our initial experience and challenges faced in integrating genomic medicine into routine clinical practice. Using the Illumina MiSeq Next generation sequencing (NGS) platform and an in-house developed bioinformatics pipeline/workflow, we successfully implemented clinical exome sequencing for rare disorders, complex disorders with unusual coexisting phenotypes, and multigene cancer panel testing for inherited cancer syndromes. The advantages of implementing these tests, the challenges for bioinformatics analysis and reporting, the ethical, legal, and social implications of moving from genetic to genomic counseling, and special policy issues related to implementing these tests are further discussed. The implementation of genomic medicine into our routine clinical practice has facilitated improved care for our patients, attesting to the ability of resource limited countries to improve care using advanced genomic technology.